Plant based extracts show novel sanitising effects against Escherichia coli on romaine lettuce and cucumber - Mandimutsira, Tinashe; Tirivanhu Njowa, Paul; Chingwaru, Constance; Chingwaru, Walter (Chulalongkorn Medical Journal, 2020)
Background: Consumption of ready-to-eat vegetables (RTEV) is increasing around the globe. Objective: The current study sought to assess the efficacy of extracts of selected African medicinal plants [Lannea edulis (Sond.) Engl. var. Edulis (L. edulis), Cassia abbreviata Oliv. (C. abbreviata), Solanum incanum (S. incanum) and Grewia bicolor (G. bicolor)] on removal of E. coli, an indicator of faecal contamination from Lactuca sativa L. var. longifolia (L. sativa) (Romaine lettuce) leaves, and Cucumis sativa L. (C. sativa) (cucumber) surfaces. Methods: Two cm2 square sections of lettuce and cucumber epidemal tissues were soaked in extracts of the medicinal plants (10 -1 of original extracts) for 1 hr. Washing of the RTEV with sterile water caused significant reductions in E. coli loads on lettuce or cucumber (P < 0.01) surfaces compared to unwashed controls. Results: Extracts from the medicinal plants caused reductions in E. coli loads on all both RTEV (load reduction by at least 2 log colony forming units (CFU)/cm2) (P < 0.01) without changes in surface morphology and colour. Use of extracts from L. edulis, C. abbreviata, S. incanum and G. bicolor have potential for use in sanitisation of RTEV, especially in killing, inhibiting or removing pathogenic E. coli that are transmitted via these fresh foods and products. While washing with G. bicolor resulted in significant reductions of E. coli on cucumber and lettuce surfaces, its efficacy was lowest compared to the rest of the treatments; hence, it is the least favourable of the selected medicinal plants. Soaking in the extract preparations did not lead to significant changes in odor, texture or taste of the vegetables. Conclusion: Use of extracts from these plants is suggested as a possible way to sanitise RTEV to reduce occurrence of, or contain outbreaks of diseases that are borne on these vegetables.